2005
DOI: 10.1007/s10722-003-4451-z
|View full text |Cite
|
Sign up to set email alerts
|

Differential heterosis in a natural population of Asian wild rice (Oryza rufipogon Griff.) due to reproductive strategy and edge effect

Abstract: Asian common wild rice (Oryza rufipogon) is a polycarpic perennial plant with a mixed inbreeder/outbreeder strategy. Seeds and clones are both reproductive components of the population. However, when collected in the flowering stage, the two differ substantially as to whether they have experienced natural selection directly or not. This study is aimed at evaluating mechanisms for the survival of a population by comparing genetic structure among subpopulations that are classified in terms of: (1) reproductive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…A previous study of genetic variation based on qualitative and quantitative genetic characteristics suggested the highest level of genetic differentiation was between seeds at the fringe and seeds in deep water (Kuroda et al, 2005a). Our data inferred by genetic distances calculated by multiple SSR markers suggested that there is weak differentiation between annuals and deep water perennial (Fig.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…A previous study of genetic variation based on qualitative and quantitative genetic characteristics suggested the highest level of genetic differentiation was between seeds at the fringe and seeds in deep water (Kuroda et al, 2005a). Our data inferred by genetic distances calculated by multiple SSR markers suggested that there is weak differentiation between annuals and deep water perennial (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…The present study demonstrated despite the perennial sub-populations in the center of the swamp having relatively higher genetic variation than outlying annual and perennial sub-populations, LV27 is a single population composed of annual and perennial subpopulations, which share genetic material with little restriction of gene flow. In a previous study undertaken in 1998, 19 plants (nine and ten nodes from a fringe site and inside area, respectively) and 19 seeds (nine and ten nodes from a fringe site and deep water area, respectively) and seven SSR loci were analyzed (Ho and He) (Kuroda et al, 2005a). In the present study, 14 polymorphic SSR markers were examined in 46 annuals and 73 within pond perennials.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…[47,83,84]). Annual and perennial wild rice in various parts of Asia can be found in the same area [33] and sometimes at the same site as part of a contiguous population ( [33]; first author's personal observations in Cambodia, India and Myanmar). The type of gradation in wild rice populations that can be found at some sites is illustrated (Fig.…”
Section: Indica-japonica Trend In Wild Ricementioning
confidence: 99%